Validación del método de Elisa para la cuantificacion de FSH utilizado en el laboratorio Quintanilla S.R.L. de la ciudad de Trujillo - Roca Santos, Marilyn Elizabeth (2007)
The purpose of this study was to investigate if the ELISA method used to determine the Follicle-Stimulating Hormone (FSH) by Laboratory Quintanilla S.R.L. satisfies the validation criteria. In order to this, the following parameters were evaluated: linearity, precision (repeatability and intermediate precision), accuracy, detection limit and quantification limit; these were determined according to the establishments of the FDA, ICH, IUPAC, Eurachem, y AEFI additionally, the procedures described in the reactive kit provided by DIAGNOSTIC AUTOMATION INC. were also followed. The results of this study show us that calibration curve was lineal with a correlation coefficient equal to 0.994; the statistic test of the pending confirmed the linearity. The variation coefficient in the repeatability of method study was equal to 5.73% and of system was equal to 0.69%. In the case of intermediate precision was 7.08. The accuracy of the method was demonstrated after applying the t-student test with a 95% of reliability and 8 degrees of freedom and obtaining an experimental t (1845) lower than that of the t tables (2.306). The detection and quantification limits were 1.688 mIU/mL and 5.376 mIU/mL correspondingly. This way, it was proved that the method satisfies the validation criteria